Auditory Display Applied to Research in Music and Acoustics - KOSTEK, Bożena (Archives of Acoustics, 2014)
This paper presents a relationship between Auditory Display (AD) and the domains of music and acoustics. First, some basic notions of the Auditory Display area are shortly outlined. Then, the research trends and system solutions within the fields of music technology, music information retrieval and music recommendation and acoustics that are within the scope of AD are discussed. Finally, an example of AD solution based on gaze tracking that may facilitate music annotation process is shown. The paper concludes with a few remarks about directions for further research in the domains discussed.